Risk and Return Ranking of JII Stocks Using the Single Index Model - Andini, Ade Irma Yesa; Rachmiyati, Nekky (Institute Of Advanced Knowledge and Science, 2025)
This study uses the Single Index Model for analysis to examine the risk and return ranking of stocks listed on the Jakarta Islamic Index (JII) from 2021 to 2023. The primary objective is to measure and evaluate the effectiveness of ranking in identifying lower-risk stocks with optimal returns within the JII, thus aiding investors in making informed investment choices compliant with Sharia principles. The research analyzes monthly closing price data from 17 selected stocks that consistently met listing criteria during the observation period. The key findings indicate that the average risk of the stocks chosen is 0.5550, reflecting a moderate level of risk. Conversely, the average return is reported at 0.0062, suggesting limited profitability across the index. Importantly, the analysis identifies three stocks exhibiting positive ratings based on their performance metrics, while the remaining stocks are rated negatively. In conclusion, this study highlights the importance of thorough risk-return analysis for investors in the Sharia-compliant market. The findings provide actionable insights, underscoring the potential of strategic stock selection within the Jakarta Islamic Index to enhance investment outcomes, thereby fostering greater confidence in Sharia-compliant investment options.